Liquid biopsy kinetics and detection of ERBB2 amplification/HER2-positivity in refractory hepatocellular carcinoma - Aaditya Srivant Geddam; Areeb Lutfi; Maaz Khan Afghan; Brian M. Currie; Russell Rosenblatt; Arturo B. Ramirez; Erin G. Bayer; Erika Hissong; Pashtoon Murtaza Kasi (The Journal of Liquid Biopsy)
Hepatocellular Carcinoma (HCC) is the most common primary liver carcinoma, accounting for 75–85% of all cases. For patients with advanced unresectable and/or metastatic HCC, treatment options primarily include immunotherapy combinations and/or oral tyrosine kinase inhibitors. For patients with alpha-fetoprotein (AFP) levels above 400 ng/ml, ramucirumab, an anti-VEGF agent, is also approved in the second-line setting. However, none of these therapies are based on a specific molecular marker and the role of molecular testing is limited. In fact, HCC is unique in the sense that a biopsy may not be pursued if imaging findings are classic for HCC, in the appropriate clinical context. Herein, we report a case of a patient with metastatic HCC and a huge disease burden where a circulating tumor DNA (ctDNA) liquid biopsy done as part of our standard of care serendipitously revealed a very high ERBB2 copy number amplification (>78). This was corroborated by HER2 immunohistochemical staining, which demonstrated strong diffuse membranous HER2 3+ expression; tissue next-generation sequencing also identified an ERBB2 unadjusted copy number gain of 183. Furthermore, we were able to demonstrate the feasibility of using both ctDNA and circulating tumor cells (CTCs) to determine the heterogeneity of HER2 and response to dual HER2 blockade trastuzumab/pertuzumab (MyPathway regimen). In addition to the utility of liquid biopsies increasing opportunities for precision medicine, this n-of-1 precision medicine case illustrates and reiterates the need for comprehensive panel-based NGS testing that employs both DNA/RNA for all patients with advanced or metastatic cancers. It also supports the agnostic potential of ERBB2/HER2 as an actionable marker.